Clinical Manifestations and Complications of Children With COVID-19 Compared to Other Respiratory Viral Infections: A Cohort Inpatient Study From Rio de Janeiro, Brazil - Giuliana Pucarelli-Lebreiro; Marianna Tavares Venceslau; Catherine Crespo Cordeiro; Fernanda Queiroz Maciel; Thiago Dias Anachoreta; Thalita Fernandes de Abreu; Ana Cristina Cisne Frota; Terezinha Marta Pereira Pinto Castiñeiras; Analucia Mendes da Costa; Adriana Cristina da Luz Lopes; Ludmila Nascimento Rodrigues Campos; Luiza Maria Calvano; et al. (Frontiers Media S.A., 2022)
IntroductionThe coronavirus disease-2019 (COVID-19) clinical manifestations in children and adolescents are diverse, despite the respiratory condition being the main presentation. Factors such as comorbidities and other respiratory infections may play a role in the initial presentation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This study aims to describe the epidemiological aspects, clinical, and laboratory manifestations of pediatric patients admitted to a tertiary pediatric hospital in Rio de Janeiro, diagnosed with COVID-19, and compare these with other viral conditions during the first year of the SARS-CoV-2 pandemic.MethodsAll patients under 18 years of age that were admitted with upper airway infection were enrolled and followed up for 30 days. The main dependent variable was the laboratorial diagnosis of SARS-CoV-2, and independent variables were studied through logistic regression.ResultsA total of 533 patients were recruited, and 105 had confirmed SARS-CoV-2 infection. Detection of other viruses occurred in 34% of 264 tested participants. Six patients died (two in SARS-CoV-2 infected group). The variables independently associated with COVID-19 were older age (OR = 1.1, 95% CI = 1.0-1.1), lower leukocytes count at entry (OR = 0.9, 95% CI = 0.8-0.9), and contact with suspected case (OR = 1.6, 95% CI = 1.0-2.6). Patients with COVID-19 presented higher odds to be admitted in an intensive care unit (OR = 1.99, 95% CI = 1.08-3.66).ConclusionsEven during the SARS-CoV-2 pandemic, several other respiratory viruses were present in admitted pediatric patients. Variables associated with COVID-19 infection were older age, lower leukocytes count at entry, and a domiciliary suspect contact. Although patients with COVID-19 were more frequently admitted to ICU, we did not observe higher mortality in this group.